a) Ta có: \(\left|x-3\right|=4\)
\(\Rightarrow x-3=4\) hoặc \(x-3=-4\)
_ \(x-3=4\Rightarrow x=7\)
_ \(x-3=-4\Rightarrow x=-1\)
Thay lần lượt \(x=7;x=-1\) vào \(y\) ta đc:
_ \(y=-\left|7\right|+6\) = \(-7+6=-1\)
_ \(y=-\left|-1\right|+6=-1+6=5\)
b) Lại có: \(x+y=\) \(7+\left(-1\right)=6\)
\(x+y=\) \(-1+5=4\)
c) Ta lại có: \(x-y=\) \(7-\left(-1\right)=8\)
\(x-y=-1-5=-6\)
\(\left|x-3\right|=4\) và \(y=-\left|x\right|+6\)
a) \(\Rightarrow\left[\begin{matrix}\left|x-3\right|=4\\\left|x-3\right|=-4\end{matrix}\right.\Rightarrow\left[\begin{matrix}x=7\\x=-1\end{matrix}\right.\)
Thay x và ta có :
\(\Rightarrow\left[\begin{matrix}-\left|7\right|+6=y\\-\left|-1\right|+6=y\end{matrix}\right.\left[\begin{matrix}y=-1\\y=5\end{matrix}\right.\)
b) \(x+y=\left[\begin{matrix}7+\left(-1\right)=6\\5+\left(-1\right)=4\end{matrix}\right.\)
c) \(x-y=\left[\begin{matrix}7-\left(-1\right)=8\\5-\left(-1\right)=6\end{matrix}\right.\)
Đề bài: cho: \(\left\{\begin{matrix}!x-3!=4\left(1\right)\\y=6-!x!\left(2\right)\end{matrix}\right.\)
a) (1) \(\Leftrightarrow\left[\begin{matrix}x-3=4\\x-3=-4\end{matrix}\right.\Rightarrow\left\{\begin{matrix}x=7\\x=-1\end{matrix}\right.\) thế vào (2)\(\Rightarrow\left[\begin{matrix}y=6-7=-1\\y=6-1=5\end{matrix}\right.\)
Kết luận (x,y)=(7,-1); (-1,5)
b) từ (a) suy ra \(\left[\begin{matrix}x+y=7-1=6\\x+y=-1+5=4\end{matrix}\right.\)
c) từ (a) suy ra \(\left[\begin{matrix}x-y=7-\left(-1\right)=8\\x-y=-1-5=-6\end{matrix}\right.\)
\(\left|x-3\right|=4\) và \(y=-\left|x\right|+6\)
a, \(\left|x-3\right|=4\)
\(\Rightarrow\left[\begin{matrix}x-3=4\\x-3=-4\end{matrix}\right.\Rightarrow\left[\begin{matrix}x=1\\x=-7\end{matrix}\right.\)
\(y=-\left|x\right|+6\)
Thay x vào, ta được:
\(\left[\begin{matrix}y=-\left|-7\right|+6\\y=-\left|-1\right|+6\end{matrix}\right.\)
\(\Rightarrow\left[\begin{matrix}y=-7+6\\y=-1+6\end{matrix}\right.\Rightarrow\left[\begin{matrix}y=-1\\y=5\end{matrix}\right.\)
b, Tính \(x+y\)
\(x+y=\left[\begin{matrix}7+\left(-1\right)=6\\5+\left(-1\right)=4\end{matrix}\right.\)
c, Tính \(x-y\)
\(x-y=\left[\begin{matrix}7-\left(-1\right)=9\\-1-5=-6\end{matrix}\right.\)